Lubricant Oil Bioremediation by Rhodococcus erythropolis Bacteria and Indigenous Bacteria Isolated from Water Contaminated with Lubricant Oil - Frentina Murti Sujadi; Yahya Yahya; Andi Kurniawan; Abd. Aziz Amin (Research Journal of Life Science, 2020)
The bioremediation system can be improved by using specific bacterial potential as oil-degrading bacteria which microorganisms can use hydrocarbons as a carbon source for their metabolic processes. The aim of this study is to identify R. erythropolis on degradation oil contamination and to obtain indigenous bacteria as new agent bacteria on bioremediation of oil contamination. The polluted water samples from used oil were taken from PPN Prigi, Trenggalek, East Java, Indonesia. The parameters considered were the detection and characterization of indigenous bacteria that degraded used oil. The density of bacteria was analyzed in the interval time of days 0, 2, 4, 6 and 7 and TPH was analyzed at final incubation. The results of this study indicate that the effectiveness of reducing oil concentration was used in testing the potential of bacteria from the highest was Pseudomonas aeruginosa which as indigenous bacteria isolated from water contaminated sites with application cell rate 1×108 cells/ml. It reduced of oil concentration up to 53%, and 1×106 cells/ml reduced oil concentration up to 47%. While, R. erythropolis with application cell rate 1×108 cells/ml reduced 47%. This result was found that Pseudomonas aeruginosa was effectively removed of oil concentration.